Qualidade de alimentos de origem animal servidos em unidades de educação infantil - Lima, Felipe Veríssimo de (2019)
The National School Food Policy (PNAE) is designed to meet the students of the public school, offering meals that meet nutritional requirements, good quality and safe. Knowing that there are nutritionists preparing the menu and guaranteeing the supply of a healthy diet, there is concern about the process of producing this food in school kitchens. The objective of this study was to evaluate the hygienic-sanitary conditions and the microbiological quality of the animal foods in the pre-preparation phase, present in the menu of the Infant Education Units (UEI) of the municipality of Mossoró-RN attended by the PNAE. For this, a 30% draw of the UEI was selected. After the permission of the Municipal Secretary of Education, three visits were made to the UEI: the first to explain the proposal of the work, the second on a day without notice for the application of the checklist and sample collection (beef, chicken, milk powder, water, countertops and utensils) and the third to disseminate the results and suggestions for improvements. The microbiological analyzes were: coliforms at 35ºC and 45ºC and mesophiles in all samples, and Staphylococcus spp. and Salmonella spp. in food samples. Subsequently, molecular analyzes were performed to identify and characterize Staphylococcus aureus and antibiotic resistance. The result of hygienic-sanitary classification revealed that 83% of the UEI are in bad conditions. Of the items evaluated, the "manipulators" presented the highest index of inadequacy (75%). Contamination was observed in the water used to prepare the food, a high presence of mesophiles on the counters, boards and a knife for cutting meat. In relation to food, 100% of the UEI presented Coagulase positive Staphylococcus counts. Of the 180 food samples, 96 (53.3%) were confirmed by S. aureus by PCR. Of these, 62 (64.6%) presented genes for the production of staphylococcal enterotoxins. The percentage of resistance to oxacillin and/or cefoxitin was observed in 100% of S. aureus isolates. The analyzed UEI present inadequacies that directly affect the health of more than 1,800 preschool children enrolled in exposure to contact with antibiotic-resistant bacteria, such as Methicillin-Resistant Staphylococcus aureus (MRSA)